In-Vitro Application of Pentoxifylline Preserved Ultrastructure of Spermatozoa After Vitrification in Asthenozoospermic Patients - Nabi, Ali; Khalili, Mohammad Ali; Talebi, Ali Reza; Mangoli, Esmat; Yari, Nahid; Nottola, Stefania Annarita; Miglietta, Selenia; Taheri, Fatemeh (Urology Journal, 2017)
Purpose: To evaluate the effect of in vitro application of pentoxifylline (PX) on sperm parameters and ultrastructure after vitrification in asthenozoospermic patients. Materials and methods: A total of 30 asthenozoospermic semen samples (aged 25-45 years) were divided into four groups before vitrification, after vitrification, control (without PX) and experimental (with PX). In experimental group, each sample was exposed for 30 min to 3.6mmol/l PX and the control group without any treatment apposing in 370C for 30 min. After incubation, the samples were washed and analyzed again. Vitrification was done according to straw method. Eosin-nigrosin and Papanicolaou staining were applied for assessment of sperm viability and morphology, respectively. The samples without PX and post treatment with PX were assessed by transmission electron microscopy (TEM). Results: A significant decrease in sperm motility (P ≤ .001), morphology (11.47 ± 2.9 versus 6.73 ± 2.01) and viability (73.37 ± 6.26 versus 54.67 ± 6.73) was observed post vitrification, but sperm motility (19.85 ± 4.75 versus 32.07 ± 5.58, P ≤ .001) was increased significantly following application of PX. This drug had no significant (P >.05) detrimental neither negative effect on ultrastructure acrosome, plasma membrane and coiled tail statues of spermatozoa. Conclusion: Vitrification had detrimental effects on sperm parameters, but PX reversed detrimental effects on sperm motility. However, PX had no alteration on ultrastructure morphology of human spermatozoa after vitrification.